Analisis Pengaruh Pembiayaan Syariah terhadap Perkembangan Usaha Mikro Kecil Menengah di Kota Depok - Aldesta Perwitasari Tunas; Lukytawati Anggraeni; Deni Lubis (Department of Islamic Economics, IPB University, 2014)
Micro, Small and Medium Enterprises (MSMEs) have an important role to economic growth. Most of MSMEs faced common problem, i.e lack of capital. Baitul Maal wat Tamwil (BMT) as a micro finance institution exists as an institution conducting the provision of financial services to micro and small entrepreneurs. This study analyzed MSMEs access to BMT and its impact on business development by using logistic regression and OLS (Ordinary Least Square). The analysis shows the factors that affect the access of MSMEs to Islamic micro finance of BMT are the business period, business turnover, total assets, and the amount of savings. The number of Islamic micro financing has a positive influence on the development of MSME business. Factors that affect the value of turnover are the frequency of the financing, the period of business, and the amount of financing.